Modelos série de potência zero-modificado para séries temporais com dados de contagem - Shirozono, Aimée (2019)
The goal of this work is to propose the Zero-Modified models with Power Series distribution (ZMPS) for time series with counting data. The ZMPS model have a huge portfolio of count data distributions wherein, with an appropriate link function, we can write the regression models using the ZMPS distributions similar to what is done with generalized linear models. Then, we can use the idea of the Generalized Autoregressive and Moving Average (GARMA) models to propose the Zero-Modified Power Series models for Time Series with counting data.